2019
DOI: 10.1105/tpc.19.00193
|View full text |Cite
|
Sign up to set email alerts
|

ABCC transporters mediate the vacuolar accumulation of crocins in saffron stigmas

Abstract: Compartmentation is a key strategy enacted by plants for the storage of specialized metabolites. The saffron spice owes its red color to crocins, a complex mixture of apocarotenoid glycosides that accumulate in intracellular vacuoles and reach up to 10% of the spice dry weight. We developed a general approach, based on coexpression analysis, heterologous expression in yeast (Saccharomyces cerevisiae), and in vitro transportomic assays using yeast microsomes and total plant metabolite extracts, for the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 62 publications
(96 reference statements)
0
60
0
Order By: Relevance
“…The tonoplast transporters (ABCC1 and MATE1), and GST were observed increasingly upregulated in grape berries upon kaolin foliar application towards improved anthocyanin accumulation in berry skins [27]. Recently, the roles of ABCC and MATE transporters in vacuolar accumulation of specific metabolite crocins in saffron stigmas were characterized [28]. Glutathione S-transferase (GST) tends to express only in berries and facilitates the conjugation of anthocyanins with reduced glutathione and transports them to the vacuoles [29].…”
Section: Figurementioning
confidence: 99%
“…The tonoplast transporters (ABCC1 and MATE1), and GST were observed increasingly upregulated in grape berries upon kaolin foliar application towards improved anthocyanin accumulation in berry skins [27]. Recently, the roles of ABCC and MATE transporters in vacuolar accumulation of specific metabolite crocins in saffron stigmas were characterized [28]. Glutathione S-transferase (GST) tends to express only in berries and facilitates the conjugation of anthocyanins with reduced glutathione and transports them to the vacuoles [29].…”
Section: Figurementioning
confidence: 99%
“…A glucosinolate transporter 1 (GTR1) in Arabidopsis was identified as jasmonoyl-isoleucine and gibberellin transporter based on its co-expression with jasmonate biosynthetic genes (Saito et al, 2015). Furthermore, Catharanthus roseus CrNPF2.9 was identified by co-expression analysis of the biosynthetic genes of monoterpene indole alkaloids (Payne et al, 2017), and saffron ( Crocus sativus ) CsABCC4a was revealed as a transporter for crocins by narrowing down the candidate transporter genes that were highly expressed in pistils (Demurtas et al, 2019). These reports prompted us to genetically and biochemically investigate candidate transporter genes for isoflavone and soyasaponin transport further.…”
Section: Resultsmentioning
confidence: 99%
“…Strigolactone translocation in petunia and vacuolar sequestration of crocins in saffron are mediated by ABC transporters [113,114].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%